2007
DOI: 10.1186/1471-2377-7-13
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of occupational magnetic field exposure and Alzheimer's disease: results from the California Alzheimer's Disease Diagnosis and Treatment Centers

Abstract: Background: A few studies have investigated a possible relationship between Alzheimer's disease (AD) and occupations with extremely low frequency magnetic field (MF) exposure. The purpose of this study was to further evaluate this possible association in a large patient population with expert diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…Several studies have suggested a possible association of ELF-MF with neoplastic malignancies in childhood, as well as with diseases affecting the nervous system [40,41]. In particular, ELF-MF has been associated with neurodegenerative diseases such as AD and ALS [12][13][14][15]. Epidemiological data have also highlighted the potential impact of ELF-MF exposure in brain and PD onset [15,16], although evidence is still poor and controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested a possible association of ELF-MF with neoplastic malignancies in childhood, as well as with diseases affecting the nervous system [40,41]. In particular, ELF-MF has been associated with neurodegenerative diseases such as AD and ALS [12][13][14][15]. Epidemiological data have also highlighted the potential impact of ELF-MF exposure in brain and PD onset [15,16], although evidence is still poor and controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic and toxicological studies have shown that environmental agents, mainly pesticides and heavy metals, represent primary classes of neurotoxic agents associated with PD [10,11]. More recently, several reports indicate that occupational exposure to electromagnetic fields might be associated with an increased risk of neurodegenerative diseases, mainly Alzheimer's disease (AD) and amyotrophic lateral sclerosis (ALS) [12][13][14][15]; however, the epidemiological evidence supporting an univocal association between PD and exposure to electromagnetic fields remains poor and controversial [15,16]. In this context, ELF-MF (between 1 Hz up to 100 kHz, originating from power lines and household appliances, as well as welding machines, induction heaters, and transport systems) has been the factor generating most attention in neurodegenerative etiopathogenesis, as the interaction between ELF-MF and biological systems directly involves oxidative stress, in particular through the radical-based mechanism [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that there is a possible association between ELF-MFs and malignancies in childhood and adulthood such as leukemia and nervous system tumors as well as cardiovascular and neurological disorders [Wertheimer and Leeper, 1979;IARC, 2002;Håkansson et al, 2003;Draper et al, 2005;Davanipour et al, 2007]. A number of in vivo and in vitro investigations have shown a possible co-promoter capacity of ELF-MFs on tumor growth as well as the potential effects elicited by ELF-MFs on various cellular functions [Crumpton and Collins, 2004;Simkó , 2004;Santini et al, 2005;Wolf et al, 2005;Berg and Berg, 2006;Frahm et al, 2006;Lisi et al, 2006;Palumbo et al, 2006;Gottwald et al, 2007].…”
mentioning
confidence: 97%
“…Epidemiological studies reported a link between the risks of various cancers, particularly childhood leukemia, and ELF-MF exposure [1]. Other studies suggested that exposure to magnetic fields (MFs) due to regular proximity to electrical power lines or occupational demands increased the risks of cardiovascular disease and Alzheimer's disease [2], [3]. In vitro studies have shown that ELF-MF could influence cell proliferation and cytoskeletal organization, and could induce DNA damage through the action of free radical species [4][6].…”
Section: ⅰ Introductionmentioning
confidence: 99%